1983
DOI: 10.1007/bf00204886
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of muscle and the determination of ultimate tissue size

Abstract: The factors that determine ultimate muscle size have been studied using a "model" that involves two strains of mice, which had been especially bred for "largeness" (QL) and for "smallness" (QS). The difference in muscle size was not found to be due to a difference in fibre size, but due to a difference in fibre number. The muscles from the "QL" mice contained about 30% more fibres. The reason for this increased fibre number was investigated. During early development, the fusion of mononucleated presumptive myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 30 publications
1
8
0
1
Order By: Relevance
“…A taxa de proliferação e de fusão estariam reduzidas nos animais desnutridos, mesmo que o número de mioblastos fundidos permanecesse constante para cada miotubo 32,36 . O número de miotubos secundários formados em cada músculo seria adequadamente regulado 4 , e a presença da terminação nervosa teria um papel fundamental no início da fusão de células para originar os miotubos secundários 33 .…”
Section: Discussionunclassified
“…A taxa de proliferação e de fusão estariam reduzidas nos animais desnutridos, mesmo que o número de mioblastos fundidos permanecesse constante para cada miotubo 32,36 . O número de miotubos secundários formados em cada músculo seria adequadamente regulado 4 , e a presença da terminação nervosa teria um papel fundamental no início da fusão de células para originar os miotubos secundários 33 .…”
Section: Discussionunclassified
“…Rehfeldt et al (2000, p.183) also suggested that growth selection leads to increases in myoblast and/or satellite cell proliferation rates. Increases in the proliferation rates can be indicated by following factors: higher myonuclear numbers (e.g., Knizetova et al, 1972;Penney et al, 1983;Brown and Stickland, 1994), higher DNA synthesis rate (Knizetova et al, 1972) and higher total muscle DNA content (e.g., Knizetova et al, 1972;Martin and White, 1979;Fowler et al, 1980;Campion et al, 1982;Jones et al, 1986;Mitchell and Burke, 1995). The greater expression of SCD gene transcripts in the muscle of SO lambs in relation to the MO lambs suggests a higher activity of this enzyme in SO animals.…”
Section: The Expression Of Transcripts Involved With Growth Skeletalmentioning
confidence: 97%
“…However, our discovery of myocyte death in branchial muscles argues against this hypothesis. Artificial selection for increased muscle mass and high hatching success in domestic birds can lead to increased muscle fiber number (Luff and Goldspink, 1967;Penny et al, 1983). Without a concomitant increase in the size of the motor neuron pool many of these additional muscle cells could suffer the fate we witnessed.…”
Section: Functional Significancementioning
confidence: 99%